2008
DOI: 10.1002/cncr.23904
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the embryonic lethal abnormal vision‐like protein HuR in human mesothelioma

Abstract: BACKGROUND. The human embryonic lethal abnormal vision (ELAV)‐like protein HuR is a messenger RNA (mRNA)‐binding protein that controls the stability of certain transcripts, including cyclooxygenase2 (COX‐2). METHODS. To investigate a possible contribution of dysregulation of mRNA stability to the progression of cancer and to COX‐2 over expression in mesothelioma, the authors studied expression of COX‐2 and HuR in 5 mesothelioma cell lines (MSTO, NCI, Ist‐Mes1, Ist‐Mes2, and MPP89) and in a group of 29 human me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 43 publications
4
22
0
Order By: Relevance
“…Our results are in line with previous findings of cytoplasmic overexpression of HuR in breast [19], ovarian [17], mesothelioma [16], and colorectal cancer [18], and our results indicate that subcellular localization of HuR is deregulated in a subset of lung cancers. Because angiogenesis and lymphangiogenesis correlated with cytoplasmic HuR expression, and high LVD and MVD have been shown to be linked to reduced survival in patients with lung cancer [22], one plausible explanation for this phenomenon is that HuR mediates its effect, at least in part, by induction of tumor-associated lymphangiogenesis and angiogenesis.…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…Our results are in line with previous findings of cytoplasmic overexpression of HuR in breast [19], ovarian [17], mesothelioma [16], and colorectal cancer [18], and our results indicate that subcellular localization of HuR is deregulated in a subset of lung cancers. Because angiogenesis and lymphangiogenesis correlated with cytoplasmic HuR expression, and high LVD and MVD have been shown to be linked to reduced survival in patients with lung cancer [22], one plausible explanation for this phenomenon is that HuR mediates its effect, at least in part, by induction of tumor-associated lymphangiogenesis and angiogenesis.…”
Section: Discussionsupporting
confidence: 95%
“…There are usually one or several AREs in the 3 0 UTR of these mRNAs that provide the binding sites for HuR, resulting in an increased mRNA half-life [15]. In addition, HuR gene overexpression occurs in a variety of malignant cancers and is related to tumor progression and poor prognosis in patients with mesothelioma [16], ovarian [17], and colon cancer [18]. Based on the known functions of HuR, we believe that HuR might exert an important function in cell cycle regulation, apoptosis, angiogenesis, inflammation, and tumor growth.…”
Section: Introductionmentioning
confidence: 99%
“…In cancer cells, it was previously shown that altered posttranscriptional regulation of COX-2 is mediated by increased cytoplasmic mRNA binding of the mRNA stability factor HuR (33). In malignant mesothelioma, the cytoplasmic expression of HuR was significantly correlated with high COX-2 expression and with poor survival (34). Finally, COX-2 has been proposed to exert its influence on mesangial cell proliferation in vitro by a novel mechanism involving the tumor suppressor p53 and the cell-cycle inhibitors p21 and p27 (35).…”
Section: Cyclooxygenasesmentioning
confidence: 77%
“…In cancer cells, it was demonstrated previously that altered post-transcriptional regulation of COX-2 is mediated by increased cytoplasmic mRNA binding of the mRNA stability factor HuR (Dixon et al, 2001). In MM, the cytoplasmic expression of HuR was correlated significantly with high COX-2 expression and with poor survival (Stoppoloni et al,2008). Finally, COX-2 has been proposed to exert its influence on mesangial cell proliferation in vitro by a novel mechanism involving the tumor suppressor p53 and the cell cycle inhibitors p21 and p27 (Zahner et al, 2002).…”
Section: Cyclooxygenasesmentioning
confidence: 89%